Belief Culture and Family Support are the Dominant Factors Affecting Antenatal Care Compliance in Sub-Urban, Indonesia - Hetty Ismainar, Hertanto W. Subagio, Bagoes Widjanarko, Cahyono Hadi (International Journal of Advanced Science and Technology, 2020)
The study aims to describe the most dominant factors affecting Antenatal Care (ANC) compliance.Thatwasa cross-sectional study. The populations are pregnant women in the 2nd and 3rdtrimester from four sub-districts inDumai City. A sample of 215 subjects participated in this study. Data werecollected by questionnaire. Data were analyzed using chi-square and multiple logistic regression.Bivariate analysis showed that there are six factors significantly associated with ANC compliance (p-value <0.05), i.e., attitudes, knowledge, belief culture, husband, family, and friends support. Multivariate analysis showed that the factors affected to ANC compliance were belief culture (Exp β: 2,455), family support (Exp β: 2,295), husband support (Exp β: 2,140), attitude (Exp β: 2,020) and friend support (Exp β: 1, 962).Conclusion,Five factors affectingAntenatal care compliance in sub-urban, i.e., attitude, belief culture, husband support, family, and friends support. The most dominant factors are belief culture and family support.We recommend that professional health workers develop health promotion designs and create a healthy support system taking into consideration our findings. Keywords: Attitude, Belief Culture, Family Support, Pregnant women,Shamans.